1995
DOI: 10.1172/jci117662
|View full text |Cite
|
Sign up to set email alerts
|

Development of a lipopeptide-based therapeutic vaccine to treat chronic HBV infection. I. Induction of a primary cytotoxic T lymphocyte response in humans.

Abstract: Our goal is to use peptide epitopes that are recognized by cytotoxic T lymphocytes (CTL) carried out in 26 normal subjects showed that the vaccine was safe and able to induce a primary HBV-specific CTL response. A dose-response curve was observed and five out of five subjects responded to the 500-jig dose. (J. Clin. Invest. 1995. 95:341-349.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
175
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 320 publications
(181 citation statements)
references
References 44 publications
5
175
1
Order By: Relevance
“…This indicates that the assays used were suitable to detect CTL directed against one certain epitope and at frequencies encountered in a non-persisting infection like influenza. Together with a recent report by Vitiello et al [18] and the fact that the volunteers were boosted twice, this suggests that the assays used here should have been sensitive enough to monitor a successful CTL induction.…”
Section: Induction Of Peptide-specific Ctlsupporting
confidence: 63%
See 4 more Smart Citations
“…This indicates that the assays used were suitable to detect CTL directed against one certain epitope and at frequencies encountered in a non-persisting infection like influenza. Together with a recent report by Vitiello et al [18] and the fact that the volunteers were boosted twice, this suggests that the assays used here should have been sensitive enough to monitor a successful CTL induction.…”
Section: Induction Of Peptide-specific Ctlsupporting
confidence: 63%
“…As seen with the flu peptide, the precursor frequencies against one common epitope are low and vary widely between individuals and over time in the same individual [31,36]. As Vitiello et al have shown, successful CTL induction can lead to strong cytotoxic responses [18]. Thus, although we can not rule out that a moderate HIV peptide-specific cytotoxicity was generated, we consider our results negative.…”
Section: Vaccination With a Th-and An Hiv-ctl Epitope 21mentioning
confidence: 66%
See 3 more Smart Citations